Inovasi Lubang Resapan Biopori Menggunakan Pipa Paralon sebagai Upaya Mengurangi Penumpukan Sampah Organik di Desa Margasari - Fathurrohman, Muhammad Iqbal; Erinasari, Fannia Dwi; Hawa, U'un Maliun; Farisa, Dian Tiara (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2023)
Margasari Village, Margasari District, Tegal Regency is an area with land use aimed at buildings, yard land, tegalan, rice fields, and plantations. The people of Margasari Village regarding rainwater infiltration and organic waste management have resulted in environmental problems such as garbage accumulation, puddles of water, and health problems. Therefore, the IPB KKN-T team conducts socialization activities for making and installation of biopore infiltration holes (LRB) in several areas of residents. In addition, the KKN-T team also provides counseling regarding the benefits of installing this LRB to local residents. With this socialization, it is hoped that people can manage household organic waste independently in their respective homelands so that they can give a good impact to overcome flood problems and land water reserves. Organic waste management can also reduce the buildup of garbage and make it easier for recycling and processing. In addition, with the management of organic waste in this LRB, it will be used as compost fertilizer after the trash is decomposed. The biopore counseling program in Margasari Village, Tegal began with the stages of socialization, manufacture, and installation of LRB in several residents' houses. This program gains a positive response from society related to sustainable environmental and economic preservation.